THE INFLUENCE OF TECHNOLOGY ACCEPTANCE MODEL (TAM) AND SOCIAL ENVIRONMENT ON THE DECISION TO PAY ZAKAT, INFAK, AND ONLINE ALMS IN THE COMMUNITY OF BANTEN PROVINCE - Ichsan, Nurul; Khasanah, Louwetyas (IZZI: Jurnal Ekonomi Islam, 2025)
This study aims to analyze the factors that influence the decision of the Banten community in paying zakat, infaq, and alms (ZIS) online. In this study, the data used is primary data obtained from distributing questionnaires and secondary data obtained from journals, articles, etc., with a research sample of 100 respondents from the community domiciled in the Banten Province area. This quantitative research method used in this study is multiple linear regression analysis using IBM SPSS software version 26.0. The results of this study indicate that the variables of usefulness, ease of use, and social environment have a significant partial and simultaneous influence on the decision of the Banten community in paying zakat, infaq, and alms online